Rodent population cycle as a determinant of gastrointestinal nematode abundance in a low-arctic population of the red fox - Mørk, Torill (Int J Parasitol Parasites Wildl, 2019)
We analyzed an 11-year time series (2005–2015) of parasite abundance for three intestinal nematode species in the red fox (Vulpes vulpes) as a function of the multi-annual rodent population cycle in low-arctic Norway, while correcting for other potential covariates that could influence prevalence and abundance. Rodents are paratenic and facultative intermediate hosts for the two Ascarididae species Toxascaris leonina and Toxocara canis, respectively and key prey for the red fox. Still the relative importance of indirect transmission through rodents and direct transmission through free-living stages is unclear. Abundance of these Ascarididae species in individual red foxes (N = 612) exhibited strongly cyclic dynamics that closely mirrored the 4-year rodent cycle. Negative binomial models provided evidence for a direct proportional increase in Ascarididae abundance with rodent density suggesting that predator functional response to rodent prey is the key transmission mechanism. In contrast, no cycles and constantly very low abundance were apparent for Uncinaria stenocephala – a third nematode species recorded without paratenic or intermediate stages.